PERANCANGAN SISTEM RANGKA PEMIKUL MOMEN KHUSUS PADA STRUKTUR ATAS BANGUNAN MIXED-USE âCIBADAK BUILDINGâ, ASTANAANYAR, BANDUNG - Chyntia Anggraeni, Debora
Intended to be built as a mixed-use building, “Cibadak Building” can be used as apartment, hotel, and mall. The building itself has 11 stories with total height of 46,35 meters with regular beam and column configuration. However, the building consists of two towers with three skywalks as the main connector. The skywalk bridges are not supported by any column in between its’ length and were put on a beam that act as an abutment. The building main component is reinforced concrete without shear wall, therefore, it classified as an open-frame structure. The designed structure classified as category D seismic design which has to be designed with special moment resisting frames. The objectives of this thesis are to create and thoroughly analyze structural model based on earthquake-resistant structure classification, provide the dimension of concrete structure including the details of its’ reinforcement, lap splices, and joint resistant capacity. Another objective is to provide a technical drawing based on the design results. Cibadak Building structure planning involves literature studies from of the official design code and structural engineering books along with structural modelling using several design software. The dynamic analysis and structural design refer to Indonesia national standards, SNI 1726:2012, SNI 1727:2013, SNI 1729:2015, and SNI 2847:2013 and several international standards, such as FEMA 451b and NIST, along with ASCE and ACI, where SNI codes originated from. The software that were used to execute structural analysis and design are ETABS 2017, SPCol, and SAPFIRE 2000.